#### Answer

$m=\dfrac{y-y_1}{x-x_1}$

#### Work Step by Step

Divide both sides by $x-x_1$ to find:
$\dfrac{y-y_1}{x-x_1}=\dfrac{m(x-x_1)}{x-x_1}
\\\dfrac{y-y_1}{x-x_1}=m
\\m=\dfrac{y-y_1}{x-x_1}$

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$m=\dfrac{y-y_1}{x-x_1}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.